Multidimensional Item Response Theory for Factor Structure Assessment in Educational Psychology Research - Immekus, Jason C.; Snyder, Kate E.; Ralston, Patricia A. (Frontiers in Education, 2019)
This study demonstrates the use of multidimensional item response theory (MIRT) to investigate an instrument’s factor structure. For didactic purposes, MIRT was used to assess the factor structure of the 9-item Effort Beliefs Scale (Blackwell, Trzesniewski, & Dweck, 2006), based on data obtained from 1,127 undergraduate engineering students (20.9% female) across two academic years attending a large, metropolitan university in the east south-central region of the United States at the beginning and end of the first semester of freshman year. MIRT results supported the scale’s multidimensional structure, which were compared to those based on confirmatory factor analysis. Specifically, comparisons of competing models supported the scale’s bifactor structure in which the collective item set related to a primary dimension and each item related to one of two domain-specific factors: Positive Relationship, Inverse Relationship. Furthermore, the utility of item response theory for assessing effort beliefs changes across the first semester and the relationship of IRT and observed scores is provided. The paper concludes with an overview of MIRT for scale development and dimensionality assessment to advance the reader’s awareness of its use as a psychometric tool.